Demystifying the Human Species from Behavioral Economy - Pérez Martínez, Armenio (2022)
The contributions of the Behavioral Economy contribute to demystify these statements that justify certain discriminatory behaviors of the human being. This article aims to analyze the Behavioral Economy criteria that contribute to demystifying the human essence and its harmful behaviors for the development of life on the planet. A theoretical investigation is carried out, based on the selection of classic works from the last 50 years that address the subject under study, applying theoretical methods such as analysis and synthesis. It is concluded that human rationality is limited, information is partially perceived, incompletely analyzed, and decisions are influenced by heuristics and cognitive biases, in addition to people's emotions and moods. Thus, the positions of hegemonic superiority of the human being in nature and of man over woman are demystified.